O olhar curatorial de Pietro Maria Bardi nas exposições de design no MASP - Buonano, Débora Gigli (2016)
This doctoral research project is a study of the critical texts of Pietro Maria Bardi on design exhibitions that took place at MASP, Museu de Arte de São Paulo Assis Chateaubriand, the period in which he was director. The study was conducted from exhibition files and they have served as a source : newspapers, magazines, books and catalogs. The research has sought to understand the importance of Bardi and his avant-garde conception of design in Brazil. The work also intends to review, through the speeches of Bardi, questions about art, craft and design and how these connections have been articulated by him in museum shows and their rehearsals.